2021
DOI: 10.1101/gr.275372.121
|View full text |Cite
|
Sign up to set email alerts
|

Mutability of mononucleotide repeats, not oxidative stress, explains the discrepancy between laboratory-accumulated mutations and the natural allele-frequency spectrum inC. elegans

Abstract: Important clues about natural selection can be gleaned from discrepancies between the properties of segregating genetic variants and of mutations accumulated experimentally under minimal selection, provided the mutational process is the same in the laboratory as in nature. The base-substitution spectrum differs between C. elegans laboratory mutation accumulation (MA) experiments and the standing site-frequency spectrum, which has been argued to be in part owing to increased oxidative stress in the laboratory e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 76 publications
(83 reference statements)
3
17
0
Order By: Relevance
“…Further analysis of mutation spectra revealed that G:C → A:T transitions (24.68%) and A:T → T:A transversions (22.08%) are two kinds of dominant mutations in the control group. These results are generally in line with previous findings in C. elegans, 36,37 indicating a consistency of MA in worms under normal culture conditions. Treatment of parental worms with α-endosulfan increased the MF (5.07 mutations per genome) of progeny, unveiling the mutagenic effects of α-endosulfan on germ cells.…”
Section: ■ Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further analysis of mutation spectra revealed that G:C → A:T transitions (24.68%) and A:T → T:A transversions (22.08%) are two kinds of dominant mutations in the control group. These results are generally in line with previous findings in C. elegans, 36,37 indicating a consistency of MA in worms under normal culture conditions. Treatment of parental worms with α-endosulfan increased the MF (5.07 mutations per genome) of progeny, unveiling the mutagenic effects of α-endosulfan on germ cells.…”
Section: ■ Discussionsupporting
confidence: 93%
“…Further analysis of mutation spectra revealed that G:C → A:T transitions (24.68%) and A:T → T:A transversions (22.08%) are two kinds of dominant mutations in the control group. These results are generally in line with previous findings in C. elegans , , indicating a consistency of MA in worms under normal culture conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Our first finding is that the two M matrices of the N2 and PB306 genotypes are similar in size and orientation, though the N2 M matrix tends to be larger and more eccentric than the one from PB306. This result is in itself not too surprising given that both genotypes showed similar mutation rates and molecular spectra, except perhaps for the X chromosome, when a subset of MA lines from the two genotypes were whole-genome sequenced (Denver et al, 2012; Rajaei et al, 2021). Another study using the same two sets of MA lines used here showed that the mutational correlations between vulval and fitness-related traits, when significant, was similar in sign and magnitude among genotypes (Braendle et al, 2010).…”
Section: Discussionmentioning
confidence: 76%
“…Even though our model is based on human mutations, similar variation is seen in other species. In addition to the 75-fold trinucleotide mutability variation found in mismatch-repair-deficient Bacillus subtilis ( Sung et al 2015 ), we calculated similar trinucleotide mutability models for other organisms with sufficiently large mutation accumulation data sets and found 20-fold global mutability variation in Chlamydomonas reinhardtii ( Ness et al 2015 , n = 6,843), 12-fold in Saccharomyces cerevisiae ( Zhu et al 2014 , n = 867), 9–21-fold in Caenorhabditis elegans ( Rajaei et al 2021 , n = 770–3,434), and 55-fold in Mus musculus ( Lindsay et al 2019 , n = 764). Therefore, although the results we present here are focused on a human model, it seems reasonable that similar processes could apply across a broad range of organisms.…”
Section: Resultsmentioning
confidence: 99%